2020
DOI: 10.1155/2020/5820749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictive Factors of Lower Extremity Deep Vein Thrombosis in Relative High-Risk Patients after Neurosurgery: A Retrospective Study

Abstract: Introduction. It is acknowledged that patients undergoing neurosurgery with neurological illness are at higher risk of lower extremity deep vein thrombosis (DVT). As an underlying life-threatening complication, the incidence and risk factors for high-risk patients with lower extremity deep vein thrombosis are still controversial in relative high-risk patients after neurosurgery. Materials and Methods. A total of 204 patients who underwent neurosurgery and were considered as a high-risk group of DVT according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…found that hypertension (Odd’s ratio [OR] – 3.2, 95% CI: 1.46–6.82; P = 0.003) and high post-operative D-dimer (OR - 1.2, 95% CI: 1.02–1.48; P = 0.034) were the independent risk factors for the occurrence of DVT following neurosurgery. [ 16 ] In our study, the sample population was relatively younger (mean age – 44 years), without major comorbidities (ASA 1–58%), and with no major motor weakness (power in each of the limbs ≥4 was noted in 90% of patients). These could be the reasons for the low incidence of DVT noted in our study.…”
Section: Discussionmentioning
confidence: 91%
“…found that hypertension (Odd’s ratio [OR] – 3.2, 95% CI: 1.46–6.82; P = 0.003) and high post-operative D-dimer (OR - 1.2, 95% CI: 1.02–1.48; P = 0.034) were the independent risk factors for the occurrence of DVT following neurosurgery. [ 16 ] In our study, the sample population was relatively younger (mean age – 44 years), without major comorbidities (ASA 1–58%), and with no major motor weakness (power in each of the limbs ≥4 was noted in 90% of patients). These could be the reasons for the low incidence of DVT noted in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Eleven studies reported patients both subjected to intracranial and spinal surgery (intracranial/spinal). Eight studies diagnosed DVT on clinical grounds [ 7 , 10 , 13 , 14 , 38 , 41 43 ], and sixteen studies diagnosed DVT based on systematic screening methods, using D-dimer [ 16 , 18 , 19 , 21 , 30 , 36 ], DUS [ 1 3 , 6 , 8 , 16 , 18 21 , 25 , 30 , 34 36 , 47 ], or CT [ 47 ]. One study evaluated both on clinical grounds and performed routine screening (DUS/CT), with the purpose of comparing the two methods [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis yielded 14 studies with a low risk of bias (Tables 1 and 2 , printed in bold; Table 5 ) [ 1 , 2 , 6 , 10 , 16 , 19 21 , 25 , 30 , 34 , 35 , 40 , 41 ]. In these studies, the reported incidence of VTE was 4.0% (clinical evaluation) in patients not receiving antithrombotic prophylaxis [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, multiple literature articles identified D-dimer as a reliable marker for detecting DVT. [25][26][27][28] Wells PS et al [29] believed that DVT may be ruled out in patients who were less likely to have deep venous thrombosis, with a negative result in the D-dimer test. Ultrasonography may be omitted in such patients.…”
Section: Discussionmentioning
confidence: 99%